Mutations at the same residue (R50) of Kir6.2 (KCNJ11) that cause neonatal diabetes produce different functional effects. - Shimomura, K; Girard, C; Proks, P; Nazim, J; Lippiat, J; Cerutti, F; Lorini, R; Ellard, S; Hattersley, A; Barbetti, F; Ashcroft, F (2006)
Heterozygous mutations in the human Kir6.2 gene (KCNJ11), the pore-forming subunit of the ATP-sensitive K(+) channel (K(ATP) channel), are a common cause of neonatal diabetes. We identified a novel KCNJ11 mutation, R50Q, that causes permanent neonatal diabetes (PNDM) without neurological problems. We investigated the functional effects this mutation and another at the same residue (R50P) that led to PNDM in association with developmental delay. Wild-type or mutant Kir6.2/SUR1 channels were examined by heterologous expression in Xenopus oocytes. Both mutations increased resting whole-cell currents through homomeric and heterozygous K(ATP) channels by reducing channel inhibition by ATP, an effect that was larger in the presence of Mg(2+). However the magnitude of the reduction in ATP sensitivity (and the increase in the whole-cell current) was substantially larger for the R50P mutation. This is consistent with the more severe phenotype. Single-R50P channel kinetics (in the absence of ATP) did not differ from wild type, indicating that the mutation primarily affects ATP binding and/or transduction. This supports the idea that R50 lies in the ATP-binding site of Kir6.2. The sulfonylurea tolbutamide blocked heterozygous R50Q (89%) and R50P (84%) channels only slightly less than wild-type channels (98%), suggesting that sulfonylurea therapy may be of benefit for patients with either mutation.